(untitled) (Journal of actual problems of jurisprudence, 2018)
In the given article is considered social safety and public order as an immeadiate criminal object provided by article 255 of the criminal code of the Republic of Kazakhstan, defined the special social danger of considered types of crimes. The ancestral and immediate objects of theft of weapons a established. The ways of improving of criminal legislation in the given sphere are proposed. The theoretical positions, called to ensure further development of criminal law science. Keys words: social safety, theft of weapons, object of crime, criminal law, arms traffic.